Biological control of spoilage and pathogens moulds in culture medium and Beninese traditional cheese wagashi by essential oil. - SESSOU, PHILIPPE; FAROUGOU, SOUAÏBOU; YEHOUENOU, BONIFACE B.; AGNIWO, BIENVENU; ALITONOU, GUY ALAIN; AZOKPOTA, PAULIN; YOUSSAO ABDOU KARIM, ISSAKA; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2013)
The investigation highlighted the antifungal effectiveness in culture medium and traditional cheese wagashi foodsystem of Syzygium aromaticum (Eugenia caryophyllata) essential oil (EO) against spoilage and toxinogenic moulds isolated from wagashi produced in Benin. The chemical composition of the EO obtained by hydrodistillation, characterized through GC-FID and GC-MS analysis, revealed eugenol (75.2%) and trans-caryophyllene (12.0%) as major components. The evaluation of in vitro antifungal activity of this oil showed a significant fungistatic activity against Aspergillus (flavus, tamarii, niger, aculeatus, ustus, terreus), Penicillium (brevicompactum, citrinum, griseofulvum), Fusarium (poae, verticillioides) and Scopulariopsis brevicaulis with MIC ranged from 200 to 600 mg/L due probably to its richness in eugenol. Moreover, this EO had fungicidal activity against Aspergillus terreus and S. brevicaulis which were the most sensitive respectively at 600 and 400 mg/L. The assessment of antifungal activity of the oil studied in wagashi foodsystem against the less sensible isolates at in vitro assay revealed high sporale reduction rate (55% at least at 1000 mg/L) on all species investigated above all on Penicillium citrinum and Aspergillus aculeatus, two harmful mycotoxins producers in cheese. Results obtained indicate the possibility of exploiting S. aromaticum EO to preserve wagashi against moulds contamination and probably mycotoxins inhibition during wagashi storage.
Keywords: Syzygium aromaticum; essential oil; antifungal activity; wagashi; Benin